Komunikasi partisipatif masyarakat Suku Akit kepada pemerintah dalam pengelolaan hutan mangrove di Kecamatan Bantan Kabupaten Bengkalis - Putra, Wendi Harla (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study examines the participatory communication between the village government and the Akit Tribe community in managing mangrove forests in Bantan District, Bengkalis Regency. The research focuses on the role of dialogue, voice empowerment, and emancipatory education in encouraging community participation. Prior research emphasizes that active community involvement in natural resource management is crucial for environmental sustainability. This study aims to analyze how dialogue, voice empowerment, and emancipatory education are applied by the Akit Tribe in managing mangrove forests. A qualitative approach with a case study design was used, collecting data through observation and in-depth interviews. The findings show that the dialogue process has been effective, though communication barriers persist. The indigenous community also utilizes media for information sharing and community activities, while emancipatory education plays a key role in empowering the Akit Tribe in managing mangrove forests.